Digital-consulting: features of digital transformation in the field of consulting - A. A. Yussuf (Publishing House of the State University of Management, 2020)
The leading direction in the field of consulting: digital-consulting, which appeared in the conditions of transformation of the traditional economy into a digital one, has been considered. An attempt has been made to determine the essence of digital consulting, to identify priority areas for the development of consulting companies in the era of digitalization, which was the purpose of the work. The main stages of the formation and changes in the field of consulting taking into account trends in the global economy have been noted. Specific features and development opportunities of a consulting company that reflect the essence of digital transformation in this area have been defined and presented in the form of a consulting model 4.0. The results of studying the development of this market, including digital consulting in market leading companies, have been presented. It has been concluded about the importance of the transition to the digital transformation according to the Consulting 4.0 model, using all the features of the digital-consulting formation stage, in order to achieve digital leadership. The research results can be used to expand and systematize scientific knowledge in the field of digital consulting, as well as to determine strategic guidelines for the development of consulting organizations in the context of digitalization.